Age-Related Temporal Processing Deficits in Word Segments in Adult Cochlear-Implant Users - Xie, Zilong (Trends Hear, 2019)
Aging may limit speech understanding outcomes in cochlear-implant (CI) users. Here, we examined age-related declines in auditory temporal processing as a potential mechanism that underlies speech understanding deficits associated with aging in CI users. Auditory temporal processing was assessed with a categorization task for the words dish and ditch (i.e., identify each token as the word dish or ditch) on a continuum of speech tokens with varying silence duration (0 to 60 ms) prior to the final fricative. In Experiments 1 and 2, younger CI (YCI), middle-aged CI (MCI), and older CI (OCI) users participated in the categorization task across a range of presentation levels (25 to 85 dB). Relative to YCI, OCI required longer silence durations to identify ditch and exhibited reduced ability to distinguish the words dish and ditch (shallower slopes in the categorization function). Critically, we observed age-related performance differences only at higher presentation levels. This contrasted with findings from normal-hearing listeners in Experiment 3 that demonstrated age-related performance differences independent of presentation level. In summary, aging in CI users appears to degrade the ability to utilize brief temporal cues in word identification, particularly at high levels. Age-specific CI programming may potentially improve clinical outcomes for speech understanding performance by older CI listeners.